STRATEGI MARKETING MIX DI PT. SEMEN INDONESIA PABRIK TUBAN - Fadali Rahman; Mad Yunus; Ahmad Nuruddin Hasbullah; Muhammad Sa’ud; Ainurrahman (STAI AN-NAJAH INDONESIA MANDIRI, 2022)
This research seeks to find out about marketing strategy at Semen Indonesia corporation. This study uses qualitative methods, with the type of case study research, in which data collection techniques are used in observation and documentation using primary and secondary data sources according to the research title. the discussion in this study is focused on marketing at Semen Indonesia corporation. Observations ware carried out by participating in the kajlan program held by the research object. the resoult of this study provide information related to what kind of marketing planning is carried out by Semen Indonesia corporation as well as what are the parts in the marketing plan. References Alma, B. (2013). Menejemen Pemasaran Dan Pemasaran Jasa. Bandung: Alfabeta. Hidayat, Syarif. Semen: jenis & aplikasinya. Kawan Pustaka, 2009. Kotler. P., & Amstrong, G. (2016) Principle Of Marketing. New Jersey: Pearson Prentice Hall, Inc. Kotler. P., & Keller K. L. (2016). Marketing Menegemen (15 Ed.) New Jersey Pearson Prentice Hall, Inc. Kunaifi, Aang. Manajemen Pemasaran Syari’ah Pendekatan Human Spirit; Konsep, Etika, Strategi, dan Implementasi. 1 ed. Vol. 1. 1 1. Yogyakarta: Maghza Pustaka, 2016. Listyawati, Indri Hastuti.